Incorporation of Nitrogen Defects for Efficient Reduction of CO2 via Two-Electron Pathway on Three-Dimensional Graphene Foam - Wu, Jingjie; Liu, Mingjie; Sharma, Pranav P; Yadav, Ram Manohar; Ma, Lulu; Yang, Yingchao; Zou, Xiaolong; Zhou, Xiao-Dong; Vajtai, Robert; Yakobson, Boris I; Lou, Jun; Ajayan, Pulickel M (Nano letters, 2016)
The practical recycling of carbon dioxide (CO2) by the electrochemical reduction route requires an active, stable, and affordable catalyst system. Although noble metals such as gold and silver have been demonstrated to reduce CO2 into carbon monoxide (CO) efficiently, they suffer from poor durability and scarcity. Here we report three-dimensional (3D) graphene foam incorporated with nitrogen defects as a metal-free catalyst for CO2 reduction. The nitrogen-doped 3D graphene foam requires negligible onset overpotential (−0.19 V) for CO formation, and it exhibits superior activity over Au and Ag, achieving similar maximum Faradaic efficiency for CO production (∼85%) at a lower overpotential (−0.47 V) and better stability for at least 5 h. The dependence of catalytic activity on N-defect structures is unraveled by systematic experimental investigations. Indeed, the density functional theory calculations confirm pyridinic N as the most active site for CO2 reduction, consistent with experimental results.